2010
DOI: 10.1364/ol.35.000217
|View full text |Cite
|
Sign up to set email alerts
|

Fast exact scalar propagation for an in-line holographic microscopy on the diffraction limit

Abstract: In lensless digital in-line holographic microscopy, currently applied fast reconstruction techniques use approximations limiting the usable NA for optical resolution. The computational effort for an exact scalar reconstruction with straightforward algorithms depends on the relation between the desired resolution and the given pixel pitch of the detector. So there is a trade-off between achievable image resolution and required computation time. We present an exact reconstruction algorithm that guaranties optimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Recently Kanka et al also reported another reconstruction scheme which solved the aliasing problem of the spherical reference wave, enabling the use of the more rigorous angular spectrum method [31]. A computationally more efficient version of this algorithm [32] was recently demonstrated to reconstruct holograms with an NA of ~0.8. As an example, using a modulated laser with reduced coherence length can resolve a cluster of e.g., 816 nm microbeads (see Fig.…”
Section: Lensfree Digital Holographic Microscopymentioning
confidence: 99%
“…Recently Kanka et al also reported another reconstruction scheme which solved the aliasing problem of the spherical reference wave, enabling the use of the more rigorous angular spectrum method [31]. A computationally more efficient version of this algorithm [32] was recently demonstrated to reconstruct holograms with an NA of ~0.8. As an example, using a modulated laser with reduced coherence length can resolve a cluster of e.g., 816 nm microbeads (see Fig.…”
Section: Lensfree Digital Holographic Microscopymentioning
confidence: 99%
“…where  , h, r, and g is the discrete version of the same notation explained before. The usage of FFT in (10) and other version of fast-transforms described in [17] and [18], enables fast reconstruction process. Object image reconstruction that is performed based on equation 10will be refered to as the direct inversion method's image.…”
Section: B Numerical Reconstructionmentioning
confidence: 99%
“…And as second one, Kanka et al have recently proposed two approaches to provide high-contrast, high-resolution images in DIHM based on the so-called tile superposition propagation ͑TSP͒ technique. 12,13 Essentially, the TSP method is a fast propagation algorithm involving low-computer-memory consumption for exact scalar wave field propagation. The TSP algorithm divides the recorded ho-logram into a set of tiles having the same size, processes the tiles separately using conventional numerical propagation methods, and adds all the propagated tiles into a single one.…”
Section: Introductionmentioning
confidence: 99%
“…The TSP algorithm divides the recorded ho-logram into a set of tiles having the same size, processes the tiles separately using conventional numerical propagation methods, and adds all the propagated tiles into a single one. Using this strategy, Kanka et al 12,13 have demonstrated imaging capabilities in DIHM with resolutions corresponding with NA values between 0.6 and 0.7.…”
Section: Introductionmentioning
confidence: 99%